The Function of T Follicular Helper Cells in the Autoimmune Liver Diseases - Lin Li; Panyang Xu; Qi Zhou; Jiancheng Xu (Journal of Immunology Research)
T follicular helper (TFH) cells are recognized as a subtype of T cells that are involved in the germinal center formation and B cell development. When dysregulated, TFH cells may represent an important mechanism that contributes to a heightened humoral response and autoantibody production in autoimmune liver diseases (AILDs). TFH cells participate in the immune response associated with AILDs by expressing surface receptors such as programmed cell death protein-1, C-X-C motif chemokine receptor 5, and inducible T cell costimulators, as well as cytokines such as interleukin-21. TFH cells also downregulate chemokine (C-C motif) receptor 7 and promote the dysregulation of the T follicular regulatory/TFH axis. This review highlights the importance of TFH cells in AILDs.